2022
DOI: 10.1182/bloodadvances.2022007007
|View full text |Cite
|
Sign up to set email alerts
|

GRK2 regulates ADP signaling in platelets via P2Y1 and P2Y12

Abstract: The critical role of G protein–coupled receptor kinase 2 (GRK2) in regulating cardiac function has been well documented for >3 decades. Targeting GRK2 has therefore been extensively studied as a novel approach to treating cardiovascular disease. However, little is known about its role in hemostasis and thrombosis. We provide here the first evidence that GRK2 limits platelet activation and regulates the hemostatic response to injury. Deletion of GRK2 in mouse platelets causes increased platelet accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…To assess total platelet accumulation in the lung, mice were also given Alexa Fluor 750-labeled α-mouse GPIX to label platelets in vivo. The platelet-labeling antibody concentration does not cause thrombocytopenia or platelet aggregate accumulation in the lungs after intraperitoneal injection of saline (data not shown 31,32 ). Thirty minutes post-αCD9 administration, we assessed platelet count, body temperature, and lung thrombosis (Figure 2B through 2E).…”
Section: Par Signaling Is a Critical Component Of Thrombosis In A Mod...mentioning
confidence: 89%
“…To assess total platelet accumulation in the lung, mice were also given Alexa Fluor 750-labeled α-mouse GPIX to label platelets in vivo. The platelet-labeling antibody concentration does not cause thrombocytopenia or platelet aggregate accumulation in the lungs after intraperitoneal injection of saline (data not shown 31,32 ). Thirty minutes post-αCD9 administration, we assessed platelet count, body temperature, and lung thrombosis (Figure 2B through 2E).…”
Section: Par Signaling Is a Critical Component Of Thrombosis In A Mod...mentioning
confidence: 89%
“…Platelets express the P2Y12 receptor on their surface, which is a G protein-coupled receptor. When the endothelium of blood vessels is damaged, collagen fibers are exposed, leading to the binding of the platelet surface receptor P2Y12 with ADP secreted by platelets, causing a change in platelet conformation and triggering platelet aggregation response [11] . In studies on the role of P2Y12 receptor signaling in the process of cardiac remodeling in mice, it was found that compared to wild-type mice, mice with P2Y12 gene knockout had significantly prolonged bleeding time and impaired platelet aggregation [12] .…”
Section: P2y12 Receptor Signaling Pathwaymentioning
confidence: 99%
“…tyrosine protein kinase [Src kinase] and G protein‐coupled receptor kinase 2/beta adrenergic receptor kinase 1 [GRK2] ) that balance platelet activation during normal haemostasis and thus, the interplay between these two receptors is defined as more than uni‐directional or comparative receptor density. Further, there is a need for operational balance after nucleotide activation (Hardy et al, 2004 , 2005 ; Zhao et al, 2022 ). Cooperativity can also occur between P2Y 1 and the ATP‐gated ion channel P2X 1 (Jones et al, 2014 ; Tolhurst et al, 2005 ; Vial et al, 2002 ).…”
Section: Platelet P2y 1 Function In Haemostasismentioning
confidence: 99%